Effect of polyethylene glycol loxenatide on weight loss in super-obese patients with type 2 diabetes: a randomized controlled trial - Liu, Zenglin; Song, Changrong; Cai, Yunlu; Li, Zhewen; Hu, Sanyuan (Frontiers in Endocrinology, 2026)
ObjectiveTo investigate the efficacy and safety of polyethylene glycol loxenatide (PEG-Loxe) for weight reduction and metabolic improvement in super-obese patients with type 2 diabetes mellitus (T2DM).MethodThis was a single-center, single-blind, randomized, controlled clinical trial. A total of 123 study participants were enrolled and randomly assigned to the PEG-Loxe low-dose group (300 μg/week), PEG-Loxe high-dose group (400 μg/week), and placebo group. In total, 105 participants completed the study. The primary endpoint was the difference in weight reduction between groups.ResultsAll three groups had similar baseline characteristics. The least squares mean, 95% confidence interval (LSM, 95% CI) change in weight from baseline to week 24 was greater in the PEG-Loxe 300 μg group -16.34 (-19.10, -13.58) kg and PEG-Loxe 400 μg group -21.14 (-23.90, -18.37) kg compared to the placebo group -6.75 (-9.51, -3.99) kg (P < 0.001). Glycated hemoglobin levels decreased from the baseline by 0.50%, 1.02%, and 1.34% in the placebo, low-dose, and high-dose groups, respectively. The PEG-Loxe treatment group showed a significant reduction in waist circumference and increased high-density lipoprotein levels during the study period. The rate of adverse drug reactions was higher in the PEG-Loxe 400 μg group (36.11%) and the PEG-Loxe 300 μg group (25.00%) than in the placebo group (11.43%). Adverse reactions were predominantly gastrointestinal.ConclusionFor super-obese patients with T2DM, continuous treatment with PEG-Loxe for 24 weeks can effectively reduce body weight and achieve good glycemic control. Clinical Trial Registrationwww.chictr.org.cn, identifier ChiCTR2100052922.